Experiencias infantiles y trastornos en la sexualidad en jóvenes universitarias de Lima- Perú - Roa Mego, Ysis (2006)
The objectives of the present study were to determine the incidence and prevalence of the dysfunctions in the female sexuality of the representative sample of university students from Lima, as well as to specify the relationship between the infantile experiences and the dysfunctions in the sexuality. An anonymous survey was elaborated for it, containing 12 scales on diverse aspects of the female sexuality. Among the main results we emphasize the following ones: the analysis of dependability and validity of the test are good, a significant relationship exists between the infantile experiences and  the dysfunctions in the sexuality of the university youths. The data indicate that a good a relationship with the mother associates in lineal and significant way with the vital importance of the maternity and in inverse form with the indicators of neurotic symptoms and the sexual dysfunctions.